The Promise of New Entrepreneurial Models in Africa’s Digital Future - Elijah Bitange Ndemo (Lembaga Penerbit Fakultas Ekonomi dan Bisnis Universitas Trisakti, 2018)
The purpose of this paper is to underscore the importance of digital transformation in Africa and its promise to create new entrepreneurial models that will promote inclusivity in the continent’s economic, social, and political development. The trust of the paper is to establish whether the continent has the right infrastructure, policies and capacity to exploit these emerging technologies in building new entrepreneurial models. The paper uses five indigenous case studies to illustrate how some of the technologies that underpin digital transformation are applied. The case studies reveal that the most commonly applied technologies in the local cases are artificial intelligence, Internet-of-Things, machine learning, blockchain, and big data. These technologies have been used to create new business models that have never previously existed on the continent. These technologies have enhanced entrepreneurialism through streamlined supply chains. The cases also reveal that their applications, especially in agriculture, will do better than any other technology in the past. With a youthful population, Africa is ready to play a big role in technological advancements. However, some countries in the continent still have challenges in infrastructure, enabling policies and capacity building, to change the fortunes of the continent for the better.